Waste prevention through product eco-design regulation in Brazilian and European Union environmental law - Cipriano, Tasso Alexandre Richetti Pires (2018)
The present study deals with the issue of waste prevention in Brazilian and European environmental law. Prevention, understood as the taking of action before a problem arises, is unquestionably the cornerstone of environmental law. In waste law, this is no different. Yet, much as the best waste is repeatedly described as being that which is never produced, it is a commonplace both in theory and in practice of environmental law that waste prevention still remains wishful thinking. The focus of this dissertation lies on quantitative (as opposed to qualitative) prevention of waste materials (i.e. matter as opposed to energy) by improving the ecodesign of the products. By drawing on the relationship between law and economics to explain the insufficiency of the traditional approach to the environmental and waste problems, an alternative theoretical framework providing a more adequate account of, and effective solutions to, those problems is searched for. At the centre of such a framework are the contribution of ecological economics and the adoption of the so-called integrated (i.e. metabolic and life cycle) perspective in environmental regulation. Based on this theoretical reconstruction, a comparative and dogmatic legal analysis of Brazilian and European waste as well as product-related environmental law is performed. After the functions of waste law and the very legal concept of waste are revisited in light of the socalled integrated waste management paradigm, waste prevention is defined by changes in the production and consumption of products so that fewer materials (i.e. resources) are consumed. Improvements in product ecodesign are instrumental in bringing about such changes and they are best addressed by product-related regulation. A few attempts to regulate the ecodesign of products are found in the European setting, from which Brazilian environmental law could learn.